2016
DOI: 10.1186/s40463-016-0149-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the psychological morbidity of waiting for sinus surgery using a mixed methods approach

Abstract: BackgroundPatients with chronic rhinosinusitis (CRS) often have to endure significant wait times for endoscopic sinus surgery (ESS). The pyschiatric impact of placement on a waitlist for ESS has not been explored.MethodsQuestionnaires measuring CRS symptom severity and health-related anxiety and stress (SNOT-22, HADS, WPAI-GH) were sent to patients diagnosed with CRS and currently on a waitlist for ESS. Fifteen representative waitlisted patients participated in one-on-one semi-structured interviews discussing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…It is interesting to note that prolonged wait times do not alter psychological dysfunction. This observation is in keeping with a prior study from our institution, where we found that there was no correlation between the length of wait time and degree of psychological distress in CRS patients who failed AMT . Subjects felt that they had no difficulty coping with their symptoms while they waited for ESS, nor did they feel their disease‐specific symptoms contributed to feeling depressed.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is interesting to note that prolonged wait times do not alter psychological dysfunction. This observation is in keeping with a prior study from our institution, where we found that there was no correlation between the length of wait time and degree of psychological distress in CRS patients who failed AMT . Subjects felt that they had no difficulty coping with their symptoms while they waited for ESS, nor did they feel their disease‐specific symptoms contributed to feeling depressed.…”
Section: Discussionsupporting
confidence: 90%
“…Our study did not capture the SNOT‐22 at the time of surgery, and thus we cannot conclude whether preoperative disease‐specific QOL varied with wait times. The current literature reports that patients receiving ongoing medical therapy while awaiting ESS face an absolute increase in SNOT‐22 global scores during this time period . Our presumption was that patients across our cohort were equally impacted in the preoperative phase, and therefore experienced the same degree of worsening in disease‐specific QOL.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The primary symptoms of nasal polyps to emerge from these qualitative interviews were consistent with those found within the broader published research literature as well as social media sources, with nasal congestion being the consistent symptom reported across all interviews and sources. [16][17][18] Recent studies have also identified the importance of nasal congestion or obstruction, nasal drip, and loss of smell in patients with CRS with nasal polyps. 23,24 Building on the identification of symptoms as relevant to the population with nasal polyps, participants in the current study discussed their symptoms in terms of frequency, duration, and severity, providing an in-depth understanding of the symptomatology, the specific characteristics of which were not detailed within the current published literature.…”
Section: Discussionmentioning
confidence: 99%
“…jval.2019.11.005). [16][17][18] These articles reported studies conducted between 2015 and 2016 in the United Kingdom and Canada and included male and female patients 18 to 68 years of age with CRS with or without nasal polyps or fungal allergic rhinitis. Face-toface patient qualitative interviews and qualitative analysis techniques were used in each of the studies.…”
Section: Literature Reviewmentioning
confidence: 99%